Decreased immune response in undernourished rats after air pollution exposure - Kurtz, Melisa Lidia (2024)
Children are highly vulnerable subpopulation to malnutrition and air pollution. We investigate, in a rat nutritional growth retardation (NGR) model, the impact of Residual Oil Fly Ash (ROFA) on the lung immune response using in vitro and ex vivo methods. In vitro: Alveolar macrophages (AM) were isolated from Control (C) and NGR animals, cultured and treated with ROFA (1–100 µg/ml) for 24 h. Ex vivo: C and NGR rats were intranasally instilled with ROFA (1 mg/kg BW) or PBS. 24 h post-exposure AM were isolated and cultured. ROFA-treatment increased superoxide anion production and TNFα secretion in C-AM in vitro, though for NGR-AM this response was lower. A similar pattern was observed for TNFα and IL-6 secretion in ex vivo experiments. Regarding the antioxidant response, although NGR-AM showed increased Nrf2, after ROFA instillation an attenuated activation was observed. To conclude, chronic undernutrition altered AM response to ROFA affecting immune responsiveness to air pollutants.